2022
DOI: 10.2147/ijgm.s358775
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of an Endoplasmic Reticulum Stress-Related lncRNA Signature for Colon Adenocarcinoma Patients

Abstract: Purpose Endoplasmic reticulum (ER) stress has a significant effect on cancer cells. Increasing numbers of studies indicate that long non-coding RNAs (lncRNAs) promote the development of colon adenocarcinoma (COAD), but the relationship between ER stress-related lncRNAs and the prognosis of COAD remains unclear. The aim of the current study was to construct and validate an ER stress-related lncRNA prognostic signature to predict COAD prognoses. Methods Gene expression da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The prognostic value of its use in gynecological tumors has been predominantly unstudied. Several studies have developed lncRNAs associated with ER stress that predict prognosis in cancer patients (11,17,18). In breast cancer patients with high risk of poor outcomes, CAI et al identified nine ERS-associated lncRNAs (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic value of its use in gynecological tumors has been predominantly unstudied. Several studies have developed lncRNAs associated with ER stress that predict prognosis in cancer patients (11,17,18). In breast cancer patients with high risk of poor outcomes, CAI et al identified nine ERS-associated lncRNAs (11).…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer patients with high risk of poor outcomes, CAI et al identified nine ERS-associated lncRNAs (11). According to a previous study, eight ER stress-related lncrnas can be used as prognostic indicators for colorectal adenocarcinoma (17). A Cox regression analysis was performed to determine risk signature in glioma based on six ER stress-related lncRNAs, and LINC00519 silencing inhibited glioma cell migration and invasion (18).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous earlier research reports have constructed risk models that could accurately anticipate the COAD prognosis, and the majority of these models incorporate multiple functional gene sets. For instance, Chen et al developed and validated a COAD predictive risk model using a total of 8 lncRNAs that are associated with endoplasmic reticulum (ER) stress [ 30 ]. Rong H and colleagues discovered a novel genetic signature that is associated with the invasion of COAD.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the ER stress-related lncRNA signature was explored based on various bioinformatics methods, revealing that the differential genes in the high-risk group might be associated with extracellular matrix pathways. 12 These findings initially help us to explore the potential complex mechanisms of ERSGs in COAD.…”
Section: Introductionmentioning
confidence: 98%